2008
DOI: 10.2174/1874609810801020084
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits of Mongolian People, and Their Influence on Lifestyle-Related Diseases and Early Aging

Abstract: Mongolians are known to have relatively short life expectancy. In order to examine the role of dietary habits in the early aging of Mongolians, the food intake inquiry, anthropometric measurements and blood clinical tests were performed for 365 healthy inhabitants in Murun, a northern Mongolia city, and compared to those of Japanese. Murun inhibitants were found to have a characteristic dietary habit of taking large amounts of meat, milk, dairy products and wheat flour products, in contrast little vegetables, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Finally, epidemiological evidence of habit 77,78 supports the close relationship between clock genes (sleep, 19,32 breakfast, 78 and shift work 58,59 ) and telomere length 53 that is shortened by ROS 25 and obesity (Figure 4). Oxidative stress and obesity were related to short lifespan in a nutritional and clinical survey of Mongolians.…”
Section: Conscientiousness As a Predictor Of Healthspanmentioning
confidence: 71%
See 1 more Smart Citation
“…Finally, epidemiological evidence of habit 77,78 supports the close relationship between clock genes (sleep, 19,32 breakfast, 78 and shift work 58,59 ) and telomere length 53 that is shortened by ROS 25 and obesity (Figure 4). Oxidative stress and obesity were related to short lifespan in a nutritional and clinical survey of Mongolians.…”
Section: Conscientiousness As a Predictor Of Healthspanmentioning
confidence: 71%
“…Oxidative stress and obesity were related to short lifespan in a nutritional and clinical survey of Mongolians. 77 A systematic review of 153 articles revealed a relationship between obesity and skipping breakfast or eating frequency. 78…”
Section: Conscientiousness As a Predictor Of Healthspanmentioning
confidence: 99%
“…Low levels of the human Se status may be associated with a significant oxidant stress and low longevity as shown in previous reports for residents of Mongolia (Komatsu et al, 2008(Komatsu et al, , 2011. The low iodine status of Mongolia (Enhtuya, 2003) may be considered as an additional risk factor, capable to enhance Se deficiency, as Se and I metabolisms are known to be inseparably linked (Banuelos, Lin Zhu-Qing, & Yin Xuebin, 2014).…”
Section: The Human Se Statusmentioning
confidence: 88%
“…17,18) In a recent study, subjects with Parkinsonism and arthritis showed high levels of Mn and Al accumulated in their brains. 19) Chronic Mn exposure shows many pathological features in common with PD. 20,21) DA deficiency has been shown to occur in chronic Mn poisoning in squirrel monkeys and rabbits.…”
Section: Discussionmentioning
confidence: 99%